Varicella — a potential threat to maternal and fetal health - Biskupska, Maria; Małecka, Ilona; Stryczyńska-Kazubska, Joanna; Wysocki, Jacek (Ginekologia polska, 2017)
The aim of the study was to evaluate the following: i) number of midwives and nurses at risk for contracting varicella; ii) effectiveness of infectious disease prevention among healthcare personnel; iii) attitude of healthcare person-nel towards immunization. A total of 524 midwives and nurses from obstetric, neonatal, and pediatric wards were investigated. Quantitative data analysis was performed. Overall, 14.7% potentially seronegative respondents were identified. Out of those with a positive history of varicella, 6.56% contracted the disease after starting work, and > 70% had contact with the varicella-zoster virus. Overall, 9.54% of the respondents had a history of varicella, 3.12% were informed about the possibility of immunization, and 1.56% of those with a negative history of the disease were offered a state-funded vaccine. In the same group, the number of vaccinated people amounted to 13.28%, and 26.13% would accept a state-funded vaccine. Varicella may constitute a significant threat to maternal and fetal health at obstetric, neonatal, and pediatric wards, which must be considered when providing care to women in the reproductive age. Occupational health physicians should confirm the immunity status of the patients and suggest immunization to seronegative subjects. Regular workshops are necessary to update the knowledge of medical professionals and patients in order to shape their attitudes and beliefs about immunization.